Association of red cell distribution width with the risk of 3-month readmission in patients with heart failure: A retrospective cohort study - Gu, Fang; Wu, Han; Jin, Xiaoli; Kong, Cheng; Zhao, Wenyan (Frontiers in Cardiovascular Medicine, 2023)
Background In recent years, red cell distribution width (RDW) has been found to be associated with the prognosis of patients with heart failure (HF) in Western countries. However, evidence from Asia is limited. We aimed to investigate the relationship between RDW and the risk of 3-month readmission in hospitalized Chinese HF patients. Methods We retrospectively analyzed HF data from the Fourth Hospital of Zigong, Sichuan, China, involving 1,978 patients admitted for HF between December 2016 and June 2019. The independent variable in our study was RDW, and the endpoint was the risk of readmission within 3 months. This study mainly used a multivariable Cox proportional hazards regression analysis. Smoothed curve ﬁtting was then used to assess the dose-response relationship between RDW and the risk of 3-month readmission. Results In the original cohort of 1,978 patients with HF (42% male and 73.1% aged ≥70 years), 495 patients (25.0%) were readmitted within 3 months after discharge. Smoothed curve ﬁtting showed a linear correlation between RDW and the risk of readmission within 3 months. In the multivariable-adjusted model, every 1% increase in RDW was associated with a 9% increased risk of readmission within 3 months (hazard ratio = 1.09, 95% confidence interval: 1.00–1.15; P < 0.005). Conclusions A higher RDW value was significantly associated with a greater risk of 3-months readmission in hospitalized patients with HF.